Relationship between the nutritional state before the breeding period and the reproductive success in alpacas (Vicugna pacos) from the Chilean Puna - Norambuena, Cecilia; Hernández, Francisca; Alfaro, Jorge; Cárcamo, Gustavo; Olavarría, Ángela; Velasco, Miriam (Austral Journal of Veterinary Sciences, 2018)
A poor nutritional state may explain the low fertility rates of domestic camelids from Puna herds. The objective of this study was to determine the relationship between the nutritional state of alpacas before the breeding period and their reproductive success. The body live weight (BLW) and body condition score (BCS; scale from 1-5) of 35 non-pregnant non-lactating alpacas from the Caquena bofedal in Chile were registered previous to the breeding period. In addition, blood samples were collected (heparinised tubes) to determine the plasma concentration of cholesterol (CHOD-PAP method), triglycerides (GPO-PAP method) and NEFA (enzymatic colorimetric method). Pregnancy was determined by trans-rectal ultrasonography (7.5 MHz, Samsung Madison, Korea) at the end of the breeding period. Data from Pregnant and Non-Pregnant groups were compared using Mann-Whitney U test (SPSS programme; P< 0.05). Pregnant (n=20) and Non-pregnant groups (n=15) had similar BLW (47.1 ± 8.8 compared to 52.8 ± 11.1 kg, respectively; P = 0.9), BCS (3.0 ± 0.4 compared to 3.1 ± 0.4, respectively; P = 0.5), plasma cholesterol (1.0 ± 0.4 compared to 0.9 ± 0.3 mmol/l, respectively; P=0.7), triglycerides (0.3 ± 0.1 compared to 0.4 ± 0.1 mmol/l, respectively; P = 0.3), and NEFA (0.6 ± 0.4 compared to 0.8 ± 0.6 mmol/l, respectively; P = 0.1) before the breeding period. NEFA values of both groups showed evidence of negative energy balance. The nutritional state of alpacas before the breeding period did not explain the differences obtained in their reproductive success.